Genome-wide analysis of the MADS-box gene family involved in salt and waterlogging tolerance in barley (Hordeum vulgare L.) - Wang, Feifei; Zhou, Zhenxiang; Zhu, Liang; Gu, Yangyang; Guo, Baojian; Lv, Chao; Zhu, Juan; Xu, Rugen (Frontiers in Plant Science, 2023)
MADS-box transcript factors are crucial members of regulatory networks underlying multiple developmental pathways and regulatory networks in abiotic stress in plants. Studies on stress resistance-related functions of MADS-box genes are very limited in barley. To gain insight into this gene family and to elucidate their roles in salt and waterlogging stress resistance, we performed genome-wide identification, characterization and expression analysis of MADS-box genes in barley. Whole-genome survey of barley revealed 83 MADS-box genes, which were categorized into type I (Mα, Mβ and Mγ) and type II (AP1, SEP1, AGL12, STK, AGL16, SVP and MIKC*) lineage based on phylogeny, protein motif structure. 20 conserved motifs were determined and each HvMADS contained 1 to 6 motifs. Through gene duplication analysis we found tandem repeat duplication was the driven force for HvMADS gene family expansion. The expressions of 21 and 25 MADS-box family members were analysed under salt and waterlogging period treatments, respectively. Additionally, the co-expression regulatory network of 10 and 14 HvMADS genes was predicted, and we proposed HvMADS11,13 and 35 as candidate genes for further exploration of the functions in abiotic stress. The extensive annotation and transcriptome profiling reported in this study ultimately provides the basis for MADS functional characterization in genetic engineering on barley and other gramineous crops.